2016
DOI: 10.1186/s40068-016-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides exposure and the use of personal protective equipment by cocoa farmers in Ghana

Abstract: Background: The hazards of pesticide exposure have been a growing concern globally. The increase of susceptibility of farmers to pesticide intoxication is due to lack of knowledge regarding safe and proper pesticide handling. The aim of this study was to evaluate cocoa farmers' pesticide exposure by assessing the ways in which they store pesticides, operational habits exhibited during and after pesticide application and the use of personal protective equipment (PPE) during pesticide application in the Brong Ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
90
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 29 publications
15
90
1
Order By: Relevance
“…Experience in agrochemicals use and farm size have a negative significant effect on farmers' level of awareness of health implications of agrochemicals use. The negative effects of farming experience on awareness of health hazards of agrochemical use are not out of place since this finding is consistent with empirical research results by Okoffo et al [7]. Extension visit was not statistically significant and this could be that agricultural extension agents do not advise farmers on safety use of agrochemicals.…”
Section: Determinants Of Level Of Awareness Of Health Implicationssupporting
confidence: 81%
See 3 more Smart Citations
“…Experience in agrochemicals use and farm size have a negative significant effect on farmers' level of awareness of health implications of agrochemicals use. The negative effects of farming experience on awareness of health hazards of agrochemical use are not out of place since this finding is consistent with empirical research results by Okoffo et al [7]. Extension visit was not statistically significant and this could be that agricultural extension agents do not advise farmers on safety use of agrochemicals.…”
Section: Determinants Of Level Of Awareness Of Health Implicationssupporting
confidence: 81%
“…Additionally, 52.6% of the respondents adhere to the recommended dosage while 47.4% do not. According to the results obtained, only 26% of the farmers use personal protective clothes and this confirms the findings of Okoffo et al [7] that less than half of cocoa farmers (35%) in Brong-Ahafo region of Ghana put on full PPE (costume) during pesticide application. Mattah et al [21] in their research on "pesticide application among farmers in the catchment of Ashaiman Irrigation Scheme of Ghana: health implications" revealed that out of 74 farmers observed spraying pesticides on their farms, 36.5% used nose guards, 45.9% used boots, 31% used hand gloves, and 25.7% wore dresses that covered the whole body except the eyes.…”
Section: Farmers' Practices Of Usage Of Agrochemicalssupporting
confidence: 76%
See 2 more Smart Citations
“…However, there is the urgent need for farmers' attention to be drawn to the usefulness of the PPEs through practical demonstrations by extension staff. Okoffo et al (2016) reported that the influence of extension service on the use of PPE is significant enough to strengthen it in order to increase farmers' knowledge and awareness of the consequences of applying pesticides without PPE. The study showed that the age of farmers had a significant influence on their knowledge about the use of pesticides.…”
Section: Farmers' Pesticides Use Practicesmentioning
confidence: 99%